2007
DOI: 10.1029/2007gl030380
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic aerosol forcing and the structure of temperature trends in the southern Indian Ocean

Abstract: [1] Over the past decades surface warming in the southern subtropical Indian Ocean (IO) has been greater than that in other oceans. The warming penetrates to a depth of 800 m, in contrast to the off-equatorial surface warming which coexists with subsurface cooling. We examine the dynamics for this rich structure. Results from the 20th century experiments of the Intergovernmental Panel on Climate Change (IPCC) confirm that the southern subtropical IO surface-to-800 m warming is greater than that in the Pacific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 20 publications
4
46
0
Order By: Relevance
“…The SIO subsurface is cooled over the long 1960-98 period in CTRL (Fig. 3a) except the south of 25°S, where a warming temperature trend mainly due to a subtropical gyre shift caused by anthropogenic forcing (Cai et al, 2007(Cai et al, , 2010. The cooling trend occurs between 100 and 400 m near the equator to 24°S.…”
Section: Multi-decadal Variability Of the Sio Subsurface Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The SIO subsurface is cooled over the long 1960-98 period in CTRL (Fig. 3a) except the south of 25°S, where a warming temperature trend mainly due to a subtropical gyre shift caused by anthropogenic forcing (Cai et al, 2007(Cai et al, , 2010. The cooling trend occurs between 100 and 400 m near the equator to 24°S.…”
Section: Multi-decadal Variability Of the Sio Subsurface Temperaturementioning
confidence: 99%
“…This change in the IO winds is perhaps linked to anthropogenic forcing (e.g. Cai et al, 2007;. Based on the IPCC-class models' results, anthropogenic aerosols were found to play an important role in the tropical SIO subsurface cooling, since increasing aerosols results in the equatorial heat loss through the processes of strengthening the global Conveyor; an intensification of the Agulhas outflow and its retroflection; and subtropical gyre poleward shift and spin-up.…”
Section: Introductionmentioning
confidence: 99%
“…6) shows an increase (decrease) in the surface wind stress at the latitude of the ACC in the GHG (AA-induced) experiment. Note that Cai and Cowan (2007) suggested that AAs induce a positive trend in the Southern Annular Mode, and (by implication) stronger sub-polar westerly winds. This suggests that the result may be model dependent, and further work is needed to understand the underlying mechanisms.…”
Section: Aerosol-induced Change (%) Ghg-only Change (%)mentioning
confidence: 99%
“…Cai et al (2006) found that aerosols induce a strengthening of the Atlantic MOC and increase of northward cross-equatorial heat transport in the Atlantic and Pacific Oceans, with the majority of change taking place in the Atlantic Ocean. Cai et al (2007) argued further that AAs strengthen the global ocean conveyor (Gordon 1986), and thereby improve the simulated historical trends in the temperature structure of the southern Indian Ocean. These studies suggest that AAs have the potential to substantially affect ocean circulation in the southern hemisphere, as well as the northern hemisphere.…”
Section: Model and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation